Exploring the interrelationships between green manufacturing practices and Malaysian green sustainable performance - Khalili, Amjad; Ismail, Md Yusof; Abdulrazak, Siti Norhafiza (Inderscience Publishers, 2022)
Green manufacturing (GM) is deliberated an integral part of green operations management. However, little is reported about the empirical investigation of GM practices and the associated sustainable performance within Malaysian industries. This paper aims to develop a conceptual multi-dimensional GM model and explore the relationships amongst these practices in order to eliminate the existing gap in operations management contemporary literature. To accomplish this, a structured questionnaire designed and sent to key respondents’ managers. Two general hypotheses are postulated based on the developed model. Results were performed through techniques utilised from both advanced programs namely SPSS 23 and AMOS 23. Findings show that both hypotheses are supported as these are significant and there are positive linkages between GM and both financial and green performance. This paper is considered a portfolio and guide for Malaysian manufacturers in their trend to be sustainable